Epidemiology of injury and illness in 153 Australian international-level rowers over eight international seasons - Trease, L.; Wilkie, K.; Lovell, G.; Drew, M.; Hooper, I. (British Journal of Sports Medicine, 2020)
Aim: To report the epidemiology of injury and illness in elite rowers over eight seasons (two Olympiads).